Career transition plans of veterinarians in clinical practice - Kogan, Lori R.; Rishniw, Mark (Frontiers in Veterinary Science, 2024)
Objective: Gain an understanding of the career transition plans of veterinarians in clinical practice.Sample: Veterinary members of the Veterinary Information Network (VIN) working as small animal clinicians.Procedures: An electronic survey distributed via the VIN data collection portal.Results: A total of 1256 responses from veterinarians in clinical practice were analyzed, with 61% indicating they plan to decrease their clinical work, and 31% to stop entirely within the next five years. The most common reasons for these choices were to have more free time for oneself and/or family/friends (76%), to maintain good health (59%), and feeling burned out (50%). Factors that might entice them to retain their current number of clinical hours included reduced workload or shorter hours (42%), financial incentivization (38%), and improved working conditions (26%). Concerns related to retirement were common with 47% of participants in our study reported feeling concerned about the loss of professional identity, 34% reported concern about reduced social connections, and 28% reported concern as to how they would fill their time.Conclusions and Clinical Relevance: The reported desire to reduce/stop one's clinical work within the next five years by 42% of veterinarians ≤ 44 years of age, with burnout a primary predictor, offers insights into the necessity of change at the organizational, systemic (versus individual) level. The fact that many participants reported concerns related to retirement and 32% reported that they did not have adequate retirement information suggests a need for supportive services to help ensure a successful transition.